2019
DOI: 10.1542/peds.2019-1619
|View full text |Cite
|
Sign up to set email alerts
|

Acute Flaccid Myelitis in the United States: 2015–2017

Abstract: BACKGROUND: Acute flaccid myelitis (AFM) is a neurologic condition characterized by flaccid limb weakness. After a large number of reports of AFM in 2014, the Centers for Disease Control and Prevention began standardized surveillance in the United States to characterize the disease burden and explore potential etiologies and epidemiologic associations. METHODS: Persons meeting the clinical case criteria of acute flaccid limb weakness from January 1, 2015, through December 31, 2017, were classified as confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 33 publications
3
70
0
Order By: Relevance
“…Although multiple viruses are associated with AFM, growing evidence suggests that nonpolio enteroviruses and specifically EV-D68 are linked to the changes in AFM epidemiology that started in 2014 (21,22). Enteroviruses were the most common viruses in nasopharyngeal, oropharyngeal, or fecal specimens from confirmed AFM patients identified by CDC researchers, and EV-D68 was the most frequent enterovirus typed (18)(19)(20). Unlike most other viruses known to cause AFM, enteroviruses routinely circulate and can cause outbreaks during the late summer and early fall months in the United States in a pattern corresponding with the observed seasonal AFM peaks (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multiple viruses are associated with AFM, growing evidence suggests that nonpolio enteroviruses and specifically EV-D68 are linked to the changes in AFM epidemiology that started in 2014 (21,22). Enteroviruses were the most common viruses in nasopharyngeal, oropharyngeal, or fecal specimens from confirmed AFM patients identified by CDC researchers, and EV-D68 was the most frequent enterovirus typed (18)(19)(20). Unlike most other viruses known to cause AFM, enteroviruses routinely circulate and can cause outbreaks during the late summer and early fall months in the United States in a pattern corresponding with the observed seasonal AFM peaks (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…CDC staff requested sterile site (e.g., blood, serum, and cerebrospinal fluid [CSF]) and nonsterile site (e.g., respiratory and fecal) specimens from each patient and tested these specimens using algorithms described previously (18,19). With specimens from 2015 and 2016, and starting in September 2018 with all received specimens, CDC staff tested for enterovirus/ rhinovirus RNA using a 5′ nontranslated regiontargeted pan-Enterovirus real-time reverse transcription PCR assay (genus-level detection) and typed those that were positive.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Ayers et al 1 , in the current issue of Pediatrics, provide comprehensive surveillance data for the polio-like illness acute flaccid myelitis (AFM) in the United States from January 1, 2015, to December 31, 2017. Importantly, in this study, they found that among the 193 children meeting the confirmed AFM case definition during the 3-year period, 143 instances (74%) occurred in 2016, fitting within the larger epidemiological context of a biennial pattern of AFM outbreaks in the US documented from 2014 to 2018 (Fig 1).…”
mentioning
confidence: 99%
“…It is already evident in the Ayers et al 1 study and among US AFM cases overall from 2014 to 2018 that enterovirus-D68 has been the predominant pathogen detected. 1,3,4 Including the entirety of US AFM epidemiology since 2014 and focusing specifically on the peak August to October periods in even years may further demonstrate a specific association between enterovirus-D68 and AFM during outbreaks. 1,3,4 The authors point out that widespread enterovirus circulation can complicate causal attribution to enteroviruses detected from nonsterile sites in AFM cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation